Effect of Zinc Oxide, Zinc Hydroxychloride, and Tri-basic Copper Chloride on Nursery Pig Performance - H. S. Cemin; J. C. Woodworth; M. D. Tokach; S. S. Dritz; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 1,215 pigs (PIC 1050 × 280; initially 11.7 lb BW) were used in a 42-d growth trial to determine the effects of ZnO, Zn hydroxychloride (IntelliBond Z; IBZ), and tri-basic copper chloride (IntelliBond C; IBC) on growth performance of nursery pigs. Pigs were allotted by pen weight and assigned to 1 of 5 dietary treatments. Treatments consisted of added Zn as ZnO (3,000 ppm in phase 1 and 2,000 ppm in phase 2); Zn hydroxychloride (IBZ; 1,000 ppm in phase 1 and phase 2); and Cu as tri-basic copper chloride (200 ppm), alone or in combination, as follows: 1) Cu only; 2) ZnO only; 3) ZnO and Cu; 4) IBZ only; and 5) IBZ and Cu. Experimental diets were fed from d 0 to 21. From d 21 to 42, pigs were fed a common diet that contained 200 ppm Cu from tri-basic copper chloride but no additional Zn other than that provided by the trace mineral premix. From d 0 to 21, there was a tendency (P = 0.073) for interaction between Zn source and Cu for ADG, where the addition of Cu to ZnO diets increased ADG; whereas, adding Cu to IBZ diets decreased ADG. Pigs fed added ZnO had greater ADFI (P = 0.018), ADG (P = 0.033), and BW on d 21 (P = 0.042) than those fed added IBZ. From d 21 to 42, pigs previously fed diets with ZnO had greater ADFI (P = 0.040) and a tendency (P = 0.071) for poorer F/G than those previously fed Cu only. Overall, feeding diets with ZnO resulted in greater ADFI (P = 0.026) compared to feeding the diet with Cu only. There was a tendency (P = 0.053) for decreased removal rate when IBZ was added to the diet compared to only adding Cu. Overall, pigs fed diets with ZnO had greater ADFI (P = 0.048) and a tendency (P = 0.074) for increased ADG compared to pigs fed diets with added IBZ. Feed cost marginally increased (P = 0.064) with the addition of ZnO compared to IBZ. Diets with ZnO resulted in greater feed cost (P = 0.018) and a tendency for higher revenue (P = 0.062) compared to the diet with Cu only. Similarly, diets with added IBZ resulted in tendencies for greater feed cost (P = 0.070), revenue (P = 0.052), and income over feed cost (IOFC) (P = 0.071) compared to the diet with Cu only. The results suggest that there are no additive effects of Zn and Cu and no major differences in performance between pigs fed diets with added Zn or Cu. Pigs fed diets with higher levels of ZnO had improved performance compared to those fed added IBZ.
Keywords: Zn; Cu; nursery pig; growth performance